Prone position ventilation and nursing management for a patient with influenza A (H1N1)virus infection combined with hypermucoviscous Klebsiella pneumoniae infection (1例甲型H1N1流感病毒合并高黏液型肺炎克雷伯菌感染患者俯卧位通气的护理体会) - WEI Xian (魏娴); WANG Huiping (王慧萍); LIU Lu (刘璐); LI Zhen (李祯); ZHANG Zhishu (张智舒) (中西医结合护理)
This paper summarized the prone position ventilation and nursing management for a patient with influenza A (H1N1)virus infection combined with hypermucoviscous Klebsiella pneumoniae infection. Key issues of nursing included: a comprehensive nursing assessment before prone position ventilation, and considering the beginning and ending points of ventilation to ensure the safety of the treatment; Appropriate patient turning, catheter maintenance and skin care during treatment period; The analgesic management by using Richmond Agitation and Sedation Scale (RASS) and Sedation-Agitation scale (SAS) to improve patient comfort and effective ventilation; enhancing the airbag pressure management to prevent the ventilator-associated Pneumonia (VAP); observation on reflux, aspiration and gastric residual volume and ensuring nutrition support; monitoring on infection indexes to prevent catheter-related infection. (总结1例甲型H1N1流感病毒感染合并高黏液型肺炎克雷伯菌感染患者俯卧位通气的护理体会。护理要点: 做好患者的评估, 正确掌握俯卧位通气开始及结束的时机, 保证治疗的安全有效; 根据患者病情, 选择合适的翻身方式, 保护各管路, 做好皮肤护理; 运用Richmond躁动-镇静量表(RASS)和镇静-躁动评分(SAS)评分, 做好镇痛镇静管理, 提高患者的舒适度, 保障有效通气。做好气囊管理, 预防呼吸机相关性肺炎(VAP)的发生。观察患者有无反流及误吸, 做好胃残余量的监测, 保证营养供给。监测感染指标, 预防导管相关感染。)